Beyond Foreign Policy? EU Sanctions at the Intersection of Development, Trade, and CFSP - Meissner, Katharina L. (2022)
In the wake of unsettling conflicts and democratic backsliding, states and organisations increasingly respond with sanctions. The European Union (EU) is one of them: Brussels makes use of the entire toolbox in its foreign policy, and its sanctions appear in different forms—diplomatic measures, travel bans, financial bans, or various forms of economic restrictions. Yet, there is little debate between different strands in the literature on EU sanctions, in particular concerning measures under the Common Foreign and Security Policy and those pertaining to the development and trade policy fields. Our thematic issue addresses this research gap by assembling a collection of articles investigating the design, impact, and implementation of EU sanctions used in different realms of its external affairs. Expanding the definition of EU sanctions to measures produced under different guises in the development, trade, and foreign policy fields, the collection overcomes the compartmentalised approach characterising EU scholarship.